Adhesion properties of poly(ethylene oxide)-lignin blend for nanocellulose composites. (1st January 2019) - Jayaramudu, Tippabattini; Ko, Hyun-U.; Kim, Hyun Chan; Kim, Jung Woong; Choi, Eun Sik; Kim, Jaehwan
Abstract: In this paper, poly(ethylene oxide)-lignin (PEO-L) blends were prepared for eco-friendly nanocellulose composites and the effect of lignin content on its adhesion property was studied by using single lap joint test. The PEO-L blends were prepared by blending method using 60% methanol. Cellulose nanofiber (CNF) film, chosen as an adherent material of eco-friendly nanocellulose composites, was prepared by casting CNF emulsion, followed by vacuum filtration and drying. The successful formation of PEO-L blends was confirmed from FTIR, DSC and XRD studies. The shear strength of PEO-L blend increased with the lignin content and the 30% lignin case (442 kPa) showed 189% larger shear strength than the pure PEO (835 kPa). This shear strength improvement is associated with enhanced hydrogen bonds between lignin/PEO and CNF film.